Artocarpus integer peel as a highly effective low-cost adsorbent for methylene blue removal: Kinetics, isotherm, thermodynamic and pelletized studies - Rosalyza, Hasan; Nurul Adina, Mohamed Razifuddin; Nurfatehah Wahyuny, Che Jusoh; Rohayu, Jusoh; Herma Dina, Setiabudi (UTM Press, 2018)
Recently, there is a growing interest in identifying low-cost alternative adsorbents which have reasonable adsorption efficiency for dye removal. In this study, agricultural waste, Artocarpus Integer peel (AI-Peel) was used as the adsorbent to remove methylene blue (MB) from aqueous solution. The batch adsorption process was conducted to evaluate the effect of contact time (1 – 40 min), adsorbent dosage (0.25 – 4.0 g L-1), pH (2 – 8), initial dye concentration (100 – 500 mg L-1) and temperature (30 – 50 oC). The experimental data followed well pseudo-second-order kinetic model and Langmuir isotherm (Type 2) with maximum adsorption capacity of 396.825 mg g-1. The analysis of thermodynamic studies indicated that the adsorption process was exothermic, controlled by a chemisorption process, feasible and spontaneous in nature with decrease in degree of spontaneity at higher temperature. The characterization results revealed that the functional groups of AI-Peel play an important role in the adsorption of MB onto AI-Peel. The study of pelletized and reusability of AI-Peel indicated the great potential of pelletized AI-Peel as low-cost adsorbent for efficient removal of MB from aqueous solution. This study successfully discovers a new highly effective low-cost adsorbent for MB removal.